Philosophy of History and the Educational Dimension (Journal of human and social sciences, 2016)
History is that branch of human knowledge which aims at collecting information about the past, verifying it, recording it, and interpreting it. It documents past events in their sequence and succession, but it does not stop at mere recording; rather, it seeks, by highlighting the interconnections among these events and clarifying the causal relationships between them, to explain the development that has occurred in the lives of nations, societies, and various civilizations, and to show how and why such development took place. Among the benefits of studying history is gaining insight into the cultures of peoples and the conditions of the past in order to draw from them lessons for the present and the future. If humanity’s goal is to continue living, it must draw upon every branch of knowledge. This would not be possible if we neglected the science that teaches us how those before us lived. Thus, through history, we live many lifetimes
Keywords: Philosophy of History; Educational Dimension; Science of History; Renaissance; Ibn Khaldun